2014
DOI: 10.1021/la5021059
|View full text |Cite
|
Sign up to set email alerts
|

Micro- and Submicrostructuring Thin Polymer Films with Two and Three-Beam Single Pulse Laser Interference Lithography

Abstract: In this work we report the application of two and three-beam single pulse laser interference lithography to thin polymer films of poly(trimethylene terephthalate) (PTT). By irradiating the sample surface with temporary and spatially overlapped single pulses from two or three coherent beams and changing the angles of incidence, we have accomplished the fabrication of large-area polymer micro and submicrogratings as well as submicrometric cavities arranged in a hexagonal lattice. The characterization of the stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 28 publications
(40 reference statements)
0
16
0
Order By: Relevance
“…This is most likely the reason why this technique is mostly used with ns-or ps-laser pulses with a longer coherence length and suitably narrow spectrum, thus limiting the range of materials that can be processed over a large area. Impressive results have been obtained on thin polymer and metal films [280,281], but also on polymers [278,282], steel and Ti-based alloys [283].…”
Section: Interference Patterningmentioning
confidence: 99%
See 1 more Smart Citation
“…This is most likely the reason why this technique is mostly used with ns-or ps-laser pulses with a longer coherence length and suitably narrow spectrum, thus limiting the range of materials that can be processed over a large area. Impressive results have been obtained on thin polymer and metal films [280,281], but also on polymers [278,282], steel and Ti-based alloys [283].…”
Section: Interference Patterningmentioning
confidence: 99%
“…(c) Topography image (5×5 µm 2 ) of the imprinted sub-micrometric cavities generated in a polymer film, with the depth profile along the red line depicted at the bottom. Adapted with permission from Ref [278],. Copyright (2014) American Chemical Society.…”
mentioning
confidence: 99%
“…This effect has been already reported by Fowlkes et al, in which laser heating has shown to induce melting of thin nickel film which results in a liquid phase and film dewetting. According to Fowlkes et al and Martín-Fabiani et al, the final shape and size of NPs depend on the laser dose, thickness of the film, and substrate properties. Upon solidification, the locally molten gold film which is accumulated in the contour of the beam is transformed into gold nanostructures of increased height.…”
Section: Resultsmentioning
confidence: 99%
“…The goal of our study is to produce small nonvolatile magnetic structures 19,20 by focusing laser irradiation on the sample surface. In these experiments we employed direct laser interference patterning (DLIP) which allows for fabrication of large-area (up to 1 cm 2 ) regular structures with periodicities down to /2 (500 nm is laser irradiation wavelength) [26][27][28][29][30][31] . The main result we report in this article is demonstration of periodic magnetic nanostructures (PMNS) produced by DLIP.…”
Section: Introductionmentioning
confidence: 99%